Sensors and Microsystems AISEM 2010 Proceedings - Neri, Giovanni; SpringerLink (Online service). (Dordrecht ; New York Springer, 2011)
This book contains a selection of papers presented at the 15th Italian Conference on Sensors and Microsystems. It provides a unique perspective on the research and development of sensors, microsystems and related technologies in Italy. In an interdisciplinary approach is taken covering topics, ranging from materials science, chemistry, applied physics, electronic engineering and biotechnologies.
Includes bibliographical references
Electronic reproduction.
Keywords: Detectors -- -- Congresses; Microelectromechanical systems -- -- Congresses